ADL Class to Improve the Digital Literacy, a Phenomenology Study Among Aisyiyah Member in Jambi - Satyawati, Niken Pupy; Gani, Rita; Sarbani, Adven; Wiguna, King Anugrah; Anwar, Citra Rosalyn (CV. Publikasi Indonesia, 2025)
tular nalar; digital literacy; interpersonal communication; elderly; Mafindo The advancement of digital technology is not in line with the adequate adaptability of the community, especially the elderly. A number of elderly people face difficulties in adopting and utilizing digital technology. Furthermore, they becomes victims of digital crime. The Elderly Digital Academy (Akademi Digital Lansia/ADL) from the Tular Nalar Program held by the Indonesian Anti-Slander Society (Mafindo) is one of the educational classes to deal with this phenomenon. With a phenomenological approach through qualitative descriptive methods, researchers conducted in-depth interviews with several Aisyiyah rmember in Jambi to explore their experiences in dealing with this phenomenon and also their experiences attending the ADL class. This study found that the materials and approaches implemented in the ADL training not only improved the digital literacy of the elderly. More than that, it was able to increase the capacity of its facilitators..